Creative Thinking Profiles of Elementary Students in Solving Mathematical Story Problems: A Descriptive Study - Kusumaningtyas, Arum; Murti, Rahayu Condro (Jurnal Pendidikan Progresif, 2025)
Creative Thinking Profile of Elementary Students in Solving Mathematics Problems. Objective: This research aimed to describe creative thinking profile of elementary school students and identified factors that influence students' creative thinking abilities in solving mathematical story problems. Methods: This research used a quantitative descriptive study to analyze students' creative thinking abilities in solving mathematical story problems on the composition and decomposition of whole numbers.   The subjects of this research were 25 fifth grade students at SD Negeri Prembulan, Galur, Kulon Progo. The data collection techniques used in this research were tests, interviews, and documentation. Meanwhile, the main instrument used in this study was a creative thinking test. Findings: The results of this research showed that the creative thinking ability of fifth grade students at SD Negeri Prembulan is still in the medium category with an average score is 6,12 out of 12 or 51% with the majority students at medium level (36%). The majority of students were still in the low category in the aspects of elaboration, fluency and originality. Meanwhile, in the elaboration aspect, the majority of students were in the medium category. From that, the most prominent aspect of creative thinking among student was the elaboration aspect, while the lowest was the originality aspect. The factors that influence students’ creative thinking abilities are lack of effort, lack of confidence on solving math problems, lack of ability, and not being used to working on open-ended questions that explore students' ideas. Conclusion: The study concluded that the students’ creative thinking ability were still in the medium category. Students’ creative thinking abilities still needed to be improved through more creative and innovative learning that is oriented towards fluency, flexibility, originality, and elaboration aspects. Keywords: creative thinking ability, whole numbers, mathematics, elementary students.